Prolyl‐isomerase Pin1 controls normal and cancer stem cells of the breast. Issue 1 (16th December 2013) - Rustighi, Alessandra; Zannini, Alessandro; Tiberi, Luca; Sommaggio, Roberta; Piazza, Silvano; Sorrentino, Giovanni; Nuzzo, Simona; Tuscano, Antonella; Eterno, Vincenzo; Benvenuti, Federica; Santarpia, Libero; Aifantis, Iannis; et al.
Abstract Mammary epithelial stem cells are fundamental to maintain tissue integrity. Cancer stem cells (CSCs) are implicated in both treatment resistance and disease relapse, and the molecular bases of their malignant properties are still poorly understood. Here we show that both normal stem cells and CSCs of the breast are controlled by the prolyl‐isomerase Pin1. Mechanistically, following interaction with Pin1, Notch1 and Notch4, key regulators of cell fate, escape from proteasomal degradation by their major ubiquitin‐ligase Fbxw7α. Functionally, we show that Fbxw7α acts as an essential negative regulator of breast CSCs' expansion by restraining Notch activity, but the establishment of a Notch/Pin1 active circuitry opposes this effect, thus promoting breast CSCs self‐renewal, tumor growth and metastasis in vivo. In human breast cancers, despite Fbxw7α expression, high levels of Pin1 sustain Notch signaling, which correlates with poor prognosis. Suppression of Pin1 holds promise in reverting aggressive phenotypes, through CSC exhaustion as well as recovered drug sensitivity carrying relevant implications for therapy of breast cancers.